The Implementation of Special Autonomy and the Role of Gampong Government: A Study of Sharia and Religious Moderation in Aceh - ZA, Safrizal; Usman, Bustami; Suswanta, Suswanta; Harirah, Zulfa; Rizki, Muhammad (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2025)
This paper discusses the role of special autonomy and village government in Aceh in supporting the implementation of sharia (Islamic law) and religious moderation. The study uses empirical qualitative methods and is analyzed through the theory of asymmetric decentralization. Data were collected through interviews with key informants, namely the Islamic Law Office, Village Head (Keuchik), Village Imam (Tengku Imum), Tuha Peut (Customary Apparatus), Pastors, Religious Figures and Community Leaders. Related literature studies include journal articles, laws and regulations, and books. The results of this study indicate that the implementation of special autonomy, especially through the framework of village government in Aceh, has effectively supported the implementation of sharia and religious moderation. This support can be seen from the authority and contribution of village government to Islamic education, such as gender-inclusive religious studies in Meunasah, economic empowerment through the management of zakat, infaq, and sedekah by Baitul Mal Gampong, and conflict resolution, namely by optimizing the active role of village officials in customary justice. It can be further emphasized that this article also concludes that promoting religious, social, and ethnic harmony through inclusive programs that actively involve all elements of society, regardless of race, religion, or ethnicity at the Gampong level is a prime example of the manifestation of effective religious moderation. Within the framework of asymmetric decentralization, Gampong authority has succeeded in supporting and facilitating special autonomy and the implementation of sharia and religious moderation can run well.